Cardiovascular Involvement in Pediatric Laminopathies. Report of Six Patients and Literature Revision - Baban, Anwar; Cicenia, Marianna; Magliozzi, Monia; Gnazzo, Maria; Cantarutti, Nicoletta; Silvetti, Massimo Stefano; Adorisio, Rachele; Dallapiccola, Bruno; Bertini, Enrico; Novelli, Antonio; Drago, Fabrizio (Frontiers in Pediatrics, 2020)
Lamin A/C (LMNA) encodes for two nuclear intermediate filament proteins. Mutations in LMNA cause a highly heterogeneous group of diseases predominantly leading to muscular or cardiac disease, lipodystrophy syndromes, peripheral neuropathy, and accelerated aging disorders. Cardiac involvement includes progressive arrhythmias (brady/tachyarrhythmias, sudden cardiac death). Furthermore, cardiomyocyte damage often progresses into dilated cardiomyopathy (DCM), rarely described in the pediatric age group. Neuromuscular manifestations are even rarer in children. We report on six pediatric patients with LMNA mutations: patient 1 was operated on for aortic coarctation, non-compact left ventricle, atrial fibrillation (AF) preceding the diagnosis of DCM; patient 2 was operated on for ventricular septal defect (VSD), developed after years malignant arrhythmias preceding the progression to DCM (left ventricular non-compaction with LV dysfunction); patient 3 had ectopic atrial tachycardia as first manifestation of a DCM; patients 4 and 5 had no major arrhythmic events but only dilated ascending aorta, mildly dilated LV with mild hypertrabeculation of the lateral wall and a normally functioning but dilated left ventricle, respectively; patient 6 showed aortic coarctation, supraventricular tachycardia. Paroxysmal AF occurred in patients 1, 2, and 3 (50% of cases). Our series highlight the coexistence of congenital heart defects (CHDs) and aortic involvement with laminopathies in four of our patients: consisting of aortic coarctation (two patients), aortic root dilatation (one patient), and VSD (one patient). Aortic changes in laminopathies have been reported only once in an adult patient. This is the first report in the pediatric setting, and no associations with CHD have been previously described.